#5 Phytocompounds in drug discovery and development: Control of cancer and antibiotic resistance - Devadasan, Velmurugan (Journal of Pharmaceutical Chemistry, 2022)
Herbal medicine is widely used globally to treat various diseases. Even though it does not lead to an immediate cure, the side effects are less compared to allopathic medicine. Cancer is one of the dreadful diseases killing millions of people worldwide. Antibiotic resistance is the major problem to tackle now as resistance had developed to many antibiotics. The Discovery of new antibiotics is very much delayed. In both problems, herbal medicine comes as a remedy. Literature shows that there are phytocompounds that can control/cure various types of cancer and also some of them act alone as antibacterials or act as adjuvants along with the resistant antibiotics in reversing the antibiotic resistance. The presentation will cover the research outcome related to the above two problems based on the work carried out in herbal medicine for the past 15 years. Details will be presented on the role of a phytocompound from a rhizome in treating colon cancer, breast cancer, and lung cancer. Some novel herbs will be discussed. To validate the above-said properties of the herbs, molecular docking had also been carried out for the related phytocompounds with relevant targets along with the drugs being used to treat the ailments.
Keywords: aaa